PENGENDALIAN HAMA TANAMAN SAYURAN DENGAN CARA MURAH, MUDAH, EFEKTIF DAN RAMAH LINGKUNGAN - ET, Prasetyani (Fakultas Pertanian Universitas Islam 45 (UNISMA) Bekasi, 2010)
Until now, farmers are still not able to break away from the use of chemical pesticides in farming seeks. The emergence of some of the negative impact of the use of chemical pesticides that eventually led to the concept of Integrated Pest Management to control pests of vegetable crops. One of the ways in the IPM concept is secaca mechanical and physical control that uses traps like sticky traps, yellow tray trap, trap the aroma, and the use of pheromone traps. Another way is to use a pesticide plant with raw materials derived from plants such as neem, citronella, ginger, soursop leaves, papaya leaves, garlic. Both methods mentioned above are very easy to implement and the result is a safe, effective, and environmentally friendly.